2019
DOI: 10.3748/wjg.v25.i37.5676
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease in patients with inflammatory bowel disease: Beyond the natural history

Abstract: BACKGROUNDNonalcoholic fatty liver disease (NAFLD) is a frequently reported condition in patients with inflammatory bowel disease (IBD). Both intestinal inflammation and metabolic factors are believed to contribute to the pathogenesis of IBD-associated NAFLD.AIMTo evaluate the prevalence of steatosis and liver fibrosis (LF) in a cohort of IBD patients and the identification of metabolic- and IBD-related risk factors for NAFLD and LF.METHODSIBD patients were consecutively enrolled from December 2016 to January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 20 publications
2
66
0
1
Order By: Relevance
“…All other drug therapies of IBD including corticosteroids were not associated with the course of NAFLD in our patients. Interestingly, in contrast, a study from 2013 identified corticosteroids as potential risk factor for NAFLD[ 10 ], while a more recent study showed no difference of steroid use in NAFLD and non-NAFLD IBD patients[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…All other drug therapies of IBD including corticosteroids were not associated with the course of NAFLD in our patients. Interestingly, in contrast, a study from 2013 identified corticosteroids as potential risk factor for NAFLD[ 10 ], while a more recent study showed no difference of steroid use in NAFLD and non-NAFLD IBD patients[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NAFLD in IBD has been shown to be around 30%–40%, thus suggesting that IBD patients might be at risk of NAFLD and NAFLD-related complications. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…NAFLD has been shown to be associated with an elevated level of circulating endotoxin that activates Kupffer cells to produce pro-inflammatory cytokines leading to hepatocyte damage 17 , which could be a result of impaired intestinal barrier function. However, although multiple factors in the pathogenesis of IBD and NAFLD have been proposed to explain high NAFLD prevalence in IBD patients and both intestinal inflammation and metabolic factors are believed to contribute to the pathogenesis of IBD-associated NAFLD, the causal relationship between these two disorders is still unclear 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%